The epidemiological trends and projected future of primary sclerosing cholangitis by 2040: An updated meta-analysis and modeling study - Meysam Olfatifar; Mohsen Rajabnia; Amir Sadeghi; Amirhassan Rabbani; Shabnam Shahrokh; Mohammad Amin Habibi; MehdiSure Pezeshgi Modarres; Mohammad Reza Zali; Hamidreza Houri (PLoS ONE, 2025)
Background and Aims Primary sclerosing cholangitis (PSC) exhibits varying incidence and prevalence rates across different regions; however, comprehensive global studies examining its geographic distribution and future trends are scarce. This study presents an updated meta-analysis through 2024 and projects the global and regional prevalence of PSC from 2024 to 2040 using an illness-death multi-state model. Methods We conducted a thorough systematic search across multiple databases to identify all primary studies published until 2024 that reported on the incidence, prevalence, and mortality rates of PSC in various regions. Using the gathered data, we developed an illness-death model to forecast the future prevalence of PSC, covering the years 2024–2040. Results Our meta-analysis revealed that the global pooled incidence and prevalence rates of PSC are 0.65 and 7.52 per 100,000 persons, respectively. Projections indicate that the global prevalence of PSC will rise to 22.98 cases per 100,000 (95% CI: 21.0–24.95), corresponding to an overall increase of 28.3%. Specifically, North America is forecasted to experience a 5.45% increase in PSC cases, reaching 24.76 cases per 100,000 (95% CI: 19.63–29.88), while Western Europe is anticipated to see a more pronounced rise of 28.79%, resulting in a prevalence of 21.48 cases per 100,000 (95% CI: 18.3–24.65) by 2040. Conclusions Our findings indicate a substantial rise in the number of individuals affected by PSC in recent years and estimate a significant future burden of the disease.